Synchrotron x-ray study of a low roughness and high efficiency K2CsSb photocathode during film growth. (24th April 2017) - Xie, Junqi; Demarteau, Marcel; Wagner, Robert; Schubert, Susanne; Gaowei, Mengjia; Attenkofer, Klaus; Walsh, John; Smedley, John; Wong, Jared; Feng, Jun; Padmore, Howard; Ruiz-Oses, Miguel; et al.
Abstract: Reduction of roughness to the nm level is critical of achieving the ultimate performance from photocathodes used in high gradient fields. The thrust of this paper is to explore the evolution of roughness during sequential growth, and to show that deposition of multilayer structures consisting of very thin reacted layers results in an nm level smooth photocathode. Synchrotron x-ray methods were applied to study the multi-step growth process of a high efficiency K2 CsSb photocathode. A transition point of the Sb film grown on Si was observed at the film thickness of 40 Å with the substrate temperature at 100 °C and the growth rate at 0.1 Å s −1 . The final K2 CsSb photocathode exhibits a thickness of around five times that of the total deposited Sb film regardless of how the Sb film was grown. The film surface roughening process occurs first at the step when K diffuses into the crystalline Sb. The photocathode obtained from the multi-step growth exhibits roughness in an order of magnitude lower than the normal sequential process. X-ray diffraction measurements show that the material goes through two structural changes of the crystalline phase during formation, from crystalline Sb to K3 Sb and finally to K2 CsSb.